Penggunaan media kartu angka bergambar untuk meningkatkan kemampuan menyelesaikan operasi hitung penjumlahan dan pengurangan pada peserta didik kelas III sekolah dasar - Salsa Alvorensa; Jenny Indrastoeti Siti Poerwanti (Universitas Sebelas Maret, 2025)
This study aimed to: 1) improve the ability to complete addition and subtraction arithmetic operations through the use of illustrated number cards; 2) describe the use of illustrated number cards to improve the ability to complete addition and subtraction arithmetic operations. This study uses the Classroom Action Research method. The subjects of this study were teachers and 21 students of grade III of SDN 2 Bakalan. Data collection techniques used were observation, interviews, documentation and tests. Data validity used triangulation. Data analysis techniques were interactive analysis. The results showed that the ability to complete addition and subtraction arithmetic operations in grade III students of SDN 2 Bakalan increased after the use of illustrated number cards in learning was implemented. This is evidenced by the percentage of completeness in the pre-action of 28.57%, then in cycle I it increased to 52.38% and in cycle II it increased to 90.47%. The average value of pre-action was 62.14, in cycle I it became 78.3 and in cycle II it increased to 85.19. The results of the study concluded that: 1) the ability to complete addition and subtraction operations of grade III students of SDN 2 Bakalan increased with the use of illustrated number cards; 2) illustrated number cards are effectively applied in learning. Theoretical implications provide information on the use of illustrated number cards in mathematics learning. Practical implications show that the use of illustrated number cards is effective and has a positive impact. This study can be a reference for other researchers.